Pulmonary Penetration of Piperacillin and Tazobactam in Critically Ill Patients. Issue 4 (13th June 2014) - Felton, T W; McCalman, K; Malagon, I; Isalska, B; Whalley, S; Goodwin, J; Bentley, A M; Hope, W W
<x xml:space="preserve">Abstract</x> Pulmonary infections in critically ill patients are common and are associated with high morbidity and mortality. Piperacillin–tazobactam is a frequently used therapy in critically ill patients with pulmonary infection. Antibiotic concentrations in the lung reflect target‐site antibiotic concentrations in patients with pneumonia. The aim of this study was to assess the plasma and intrapulmonary pharmacokinetics (PK) of piperacillin–tazobactam in critically ill patients administered standard piperacillin–tazobactam regimens. A population PK model was developed to describe plasma and intrapulmonary piperacillin and tazobactam concentrations. The probability of piperacillin exposures reaching pharmacodynamic end points and the impact of pulmonary permeability on piperacillin and tazobactam pulmonary penetration was explored. The median piperacillin and tazobactam pulmonary penetration ratios were 49.3 and 121.2%, respectively. Pulmonary piperacillin and tazobactam concentrations were unpredictable and negatively correlated with pulmonary permeability. Current piperacillin–tazobactam regimens may be insufficient to treat pneumonia caused by piperacillin–tazobactam–susceptible organisms in some critically ill patients. Clinical Pharmacology & Therapeutics (2014); 96 4, 438–448. doi:10.1038/clpt.2014.131